Enhancing Wastewater Treatment Efficiency: Utilising Saponification Products for Sustainable Cleaning Processes - Dordević, Dani; Vítězová, Monika; Vítěz, Tomáš; Dordevic, Simona; Hamšíková, Monika; Kushkevych, Ivan (Environmental microbiology reports, 2025)
This study explores the interaction of saponification products with microbial communities in aerobic and anaerobic sewage sludge from wastewater treatment plants (WWTPs). It focuses on the reutilisation of waste cooking oils into soap and evaluates the biodegradation of these products using microbial respiration activity and biological oxygen demand (BOD) as indicators. Results demonstrate that soaps degrade effectively under both aerobic and anaerobic conditions, with anaerobic degradation contributing to methane production-a valuable biofuel. Importantly, no toxic effects on sludge microorganisms were observed. The research highlights that these saponification products can be fully integrated into the wastewater treatment process without adverse effects on microbial dynamics. Moreover, the economic analysis reveals that biosurfactants derived from used oils can be produced at a cost of approximately 0.12-3.0 EUR/kg, significantly lower than the 1-20 EUR/kg typically spent on chemical coagulants or synthetic surfactants used in WWTPs. These findings support the feasibility of repurposing waste oils into environmentally friendly, cost-effective treatment additives, enhancing microbial performance and promoting circular economy practices in wastewater management.
Keywords: anaerobióza; Anaerobiosis; měření biologické spotřeby kyslíku; Soaps; povrchově aktivní látky; sustainability; Sewage; biodegradace; Surface-Active Agents; aerobióza; Aerobiosis; edible oil waste; mýdla; čištění vody; Biodegradation, Environmental; Wastewater; Waste Disposal, Fluid; Water Purification; odpadní vody; microorganism respiration; wastewater treatment efficiency; odpad tekutý - odstraňování; odpadní voda; Bacteria; Biological Oxygen Demand Analysis